Improving usability of collaborative scientific visualization systems - Casera, Steve; Nägeli, Hans-Heinrich; Kropf, Peter (: IASTED, 2006)
This paper presents the key features of a collaborative visualization system. It discusses the main challenges of remote collaboration in the case of scientific visualization and presents our solutions. Our system provides a group of geographically distributed scientists the means of sharing their data, of interactively creating visualizations, and of analyzing them. This allows for shorter turnaround times compared to a more traditional approach. Our main objectives are to improve the ease of use as well as the cognitive efficiency and to minimize the waiting time for the participants in collaborative efforts. The main challenges we identified include the support of network heterogeneity, portability, ease-of-use, privacy, configuration of the working mode, strategy for coordinating access to shared resources, and for granting, respectively controlling permissions of operation. Real-time collaboration in current distributed groupware workspaces is often a difficult and awkward process. Being aware of what the other participants of a session are doing is an important issue in such a collaboration. In scientific visualization the data volume that is involved may be huge. We present three different methods of data transfer, compare their efficiency with respect to particular application scenarios, and give results of our tests.
, 2016
Keywords: Scientific visualization; collaboration; collaborative visualization; CSCW